Experimental study and numerical simulation of impact compression mechanical properties of high strength coral aggregate seawater concrete. (March 2020) - Ma, Haiyan; Yue, Chengjun; Yu, Hongfa; Mei, Qiquan; Chen, Li; Zhang, Jinhua; Zhang, Yadong; Jiang, Xiquan
Highlights: Method for preparing high-strength coral aggregate seawater concrete with C70 strength grade. Effect of sisal fiber on impact mechanical properties of high-strength coral aggregate seawater concrete. Established a binary function relationship between DIF with strain rate and strength grade of high-strength coral aggregate seawater concrete. Energy method for describing energy absorption performance of high-strength coral aggregate seawater concrete. Simulation of CASC and analysis of Poisson's ratio at different strain rates. Abstract: Based on the mix proportion design principle of high performance lightweight aggregate concrete, rich slurry concrete theory and fiber reinforced toughening technology, high strength Coral Aggregate Seawater Concrete (CASC) and sisal fiber reinforced CASC (SFCASC) with 28d cube compressive strength of 74.6 MPa and 77.3 MPa respectively were prepared. The Ф75 mm split Hopkinson pressure bar (SHPB) was used to carry out impact compression tests on CASC and SFCASC with sisal fiber content of 3 kg/m 3, and the finite element software LS-DYNA was used to carry out numerical simulation analysis on CASC impact tests. The results show that high strength CASC has obvious strain rate effect, DIF is related to strain rate ( ε ˙ ) and concrete compressive strength ( fcu ), the relationship between DIF and strain rate recommended by the European Concrete Committee (CEB) is not applicable to high-strength CASC, the parameters of CEB model are re-fitted and the relationship between DIF and strain rate is established on the basis of the above ε ˙ and fcu ; It is found that impact incident energy, reflection energy, transmission energy and absorption energy are positively correlated with strain rate. The strain rate effect of concrete is explained from the angle of energy, and the relation between DIF and absorption energy is fitted. When the DIF of CASC and SFCASC are the same, the absorption energy of SFCASC is 49.06%–140.29% higher than that of CASC; The finite element software LS-DYNA is used to simulate three working conditions with strain rates of 62.3 s −1, 93.1 s −1 and 137.4 s −1 . The stress-strain curves and failure patterns obtained are in good agreement with the experimental results. The change of Poisson's ratio with strain rate is analyzed according to LS-DYNA numerical calculation. It is found that Poisson's ratio of CASC has no strain rate effect within the strain rate range of this paper (3 × 10 −6 –1.8 × 10 2 s −1 ).